2008
DOI: 10.2304/elea.2008.5.4.384
|View full text |Cite
|
Sign up to set email alerts
|

High School Teachers' Beliefs about Learner-Centred E-Learning

Abstract: This article reports on a study conducted to gain insight into teachers' beliefs about elearning. Data collection relied on discussions conducted with 16 teachers from six high schools in two adjacent municipalities of one Canadian province. Data collection and analysis were guided by a framework of research-validated, learner-centred principles. Teachers' beliefs portrayed learners as digital natives who actively consume information and knowledge, engage emotionally with technology, and devote themselves to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Online learner satisfaction primarily related their ability to learn from online content, interact and communicate from others, and understand to needs for success (Palmer & Holt, 2009). This finding features the structure component of the TD theory and reveals out the relation between the structure and the satisfaction (Lee, & Rha, 2009;Murphy & Rodríguez-Manzanares, 2008;Stein, Wanstreet, Calvin, Overtoom & Wheaton, 2005;Horzum, 2007).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Online learner satisfaction primarily related their ability to learn from online content, interact and communicate from others, and understand to needs for success (Palmer & Holt, 2009). This finding features the structure component of the TD theory and reveals out the relation between the structure and the satisfaction (Lee, & Rha, 2009;Murphy & Rodríguez-Manzanares, 2008;Stein, Wanstreet, Calvin, Overtoom & Wheaton, 2005;Horzum, 2007).…”
mentioning
confidence: 55%
“…Online interactive tool's usage increased SP positively (Chou & Min, 2009;Joyce & Brown, 2009;Mykota & Duncan, 2007;Weinel, Bannert, Zumbach, Hoppe & Malzahn, 2011;Wise, Chang, Duffy, & del Vale, 2004). From this aspect, interaction and SP are considered directly related two variables (Murphy & Rodríguez-Manzanares, 2008;Richardson & Swan, 2003). Related literature showed that SP has a positive effect on online learner"s satisfaction and achievement (Olpak & Çakmak, 2009).…”
Section: Social Presencementioning
confidence: 99%
See 1 more Smart Citation
“…The coder then associated statements with one of the four LCP dimensions of factors (A. Cognitive and metacognitive factors; B. Motivational and affective factors; C. Developmental and social factors; and D. Individual differences factors). To facilitate this process, the coder relied on a version of the summary of the dimensions of LCPs referred to earlier (see Murphy & Rodriguez, 2008b) that included key words for each dimension. Another individual then verified the associations.…”
Section: Methodsmentioning
confidence: 99%
“…A description of the 14 principles is available in McCombs and Vakili (1995) and Bonk and Cunningham (1998). Murphy and Rodriguez-Manzanares (2008b) provide a synthesised description of the four dimensions of the LCPs which we reproduce here:…”
Section: The Learner Centred Principlesmentioning
confidence: 99%